Mengembangkan Keterampilan Bertanya pada Anak Usia Dini Mendorong Rasa Ingin Tahu dan Pemikirian Kritis - Selvina Armiah; Kholidah Nur; Nova Elliza; Putri Salsabila (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2025)
This journal discusses the development of questioning skills in early childhood as an effort to encourage curiosity and critical thinking skills. Questioning skills are considered important in the learning process, because they can increase children's involvement and help them understand information in more depth. This research uses a quantitative approach with the early childhood population in educational institutions, and collects data through questionnaires and direct observation. The results of the research show that there is a positive influence between children's questioning skills and curiosity and critical thinking abilities. Children who are used to asking questions tend to be more active in exploration and discussion, which strengthens their understanding. The journal also identifies various strategies for developing questioning skills, such as creating a supportive environment, using open-ended questions, and encouraging group discussions. Even though there are challenges, such as limited time and children feeling uncomfortable asking questions, it is important for educators and parents to create a safe space for children to actively participate. Developing questioning skills is expected to be a crucial first step in preparing children to face future challenges, as well as increasing their creativity and critical thinking abilities.